Psychotropic medications and the risk of sudden cardiac death during an acute coronary event - Honkola, Jussi; Hookana, Eeva; Malinen, Sanna; Kaikkonen, Kari S; Junttila, M Juhani; Isohanni, Matti; Kortelainen, Marja-Leena; Huikuri, Heikki V (European heart journal, 2012)
Psychotropic medication increases cardiac mortality, but the reasons for this association are not clear. We studied the role of psychotropic drugs as a triggering factor of sudden cardiac death (SCD) during an acute coronary event. The use of medication was compared between victims of SCD and survivors of an acute coronary event in a case-control study including a consecutive series of victims of SCD (n= 1814, mean age 65 ± 11 years) verified to be due to an acute coronary event at medico-legal autopsy and consecutive series of patients surviving an acute myocardial infarction (AMI; n= 1171, mean age 66 ± 12 years). The medication history was obtained from autopsy/hospital records and interviews with relatives of SCD victims and AMI patients. The use of antipsychotics [9.7 vs. 2.4%, odds ratio (OR) 4.4, 95% confidence interval (CI) 2.9-6.6; P< 0.001] and antidepressants (8.6 vs. 5.5%, OR: 1.6, 95% CI: 1.2-2.2; P= 0.003) was more common in the SCD than AMI group, but the use of benzodiazepines did not differ between the groups (11.7 vs. 13.2%; P= 0.270). The use of antipsychotics remained as a significant risk factor for SCD after adjustment for confounding variables (OR: 3.4, 95% CI: 1.8-6.5; P< 0.001). Combined use of phenothiazines and any antidepressant was associated with a very high risk of SCD (OR: 18.3, 95% CI: 2.5-135.3; P< 0.001). The use of psychotropic drugs, especially combined use of antipsychotic and antidepressant drugs, is strongly associated with an increased risk of SCD at the time of an acute coronary event.